Social Work Perspectives on Leadership and Organisation - Wolmesjö, Maria (IntechOpen, 2023)
This edited volume, Social Work - Perspectives on Leadership and Organisation, presents a variety of perspectives and reflections from social work theories and practice on how to manage, lead and organize social work in different parts of the world. The authors share their experiences and knowledge from a variety of perspectives, focusing on education, practice, user participation, leading social work with responsibility for handling different ethical dilemmas, and organizing a sustainable and healthy work-life for both staff members and their clients. Global collaboration enables reflection on social work leadership and organization from different professional perspectives and organizational levels. The book addresses students, politicians, lecturers and researchers, practitioners, users, relatives and others who are interested in social work and want to improve their understanding of social work leadership and organization from an international perspective.